LEADERSHIP WITHIN SPORTS COMMUNITIES AND THE FACILITATION OF SOCIAL COHESION THROUGH SPORT - Hrachyk, Ohanian (Global Prosperity, 2026)
Abstract. This study proposes an integrated framework explaining the paradigm shift in elite sports management from centralized, authoritarian leadership toward a polycentric model of shared leadership and psychologically informed mentorship. Addressing the limitations of traditional “Great man” theories, the author proposes a unified operational framework for high-performance environments based on a synthesis of multidisciplinary constructs, including transformational leadership, Self-Determination Theory (SDT), the Job Demands-Resources (JD-R) model and Social Interdependence Theory. The analysis demonstrates that the augmentation effect in athletic output is achieved through the synergistic interplay of identity-based leadership, cognitive synchronization via Shared Mental Models (SMM) and the cultivation of lateral accountability buffered by psychological safety. Through the application of the author`s proprietary “Turnaround strategy” and “Pipeline model” the efficacy of this holistic ecological approach is validated in mitigating allostatic load and ensuring sustainable talent development. Ultimately, the research posits that the expert mentor functions as a pivotal node in the social fabric, facilitating the “Spillover effect” of life skills from the athletic arena to the broader community.